Աքեմենյան տերության հյուսիսարևմտյան սահմանի այսրկովկասյան հատվածի տեղորոշման շուրջ (պատմահնագիտական քննություն) - Խաչատրյան, Ժորես Դ.; Նախշքարյան, Արմեն Ֆ. (ՀՀ ԳԱԱ հրատ.)
Выявление новых археологических данных ведет к переосмыслению установившихся в исторической науке взглядов на локализацию северо-западных границ Ахеменидской империи. Между тезисами относительно локализации XI, XIV, XV сатрапий Ахеменидской империи и существующими археологическими данными наблюдается ряд противоречий. Critical interpretation of historical and archaeological sources as well as discoveries of new archaeological data may result in reformulating and redrawing the North-Western boundaries of the Achaemenid Empire, thus prompting rethinking of certain established views in historical science. There are discrepancies between the assumed localizations of the Achaemenid Satrapies №№ XI, XIV, XV and the existing archaeological data.
Keywords: Պատմություն